2015
DOI: 10.1159/000441327
|View full text |Cite
|
Sign up to set email alerts
|

The New Conceptualization of Alzheimer's Disease under the Microscope of Influential Definitions of Disease

Abstract: Background: According to its new conceptualization, Alzheimer's disease (AD) has preclinical and symptomatic phases, and biomarker abnormality justifies the diagnosis of the disease. Methods: The conceptual validity of AD is assessed on the basis of the disease definitions of T. Szasz, R.E. Kendell and J.G. Scadding, C. Boorse, K.W.M. Fulford and J.C. Wakefield, as well as of the DSM-5 classification system. Results: The new AD conceptualization could fit the Szaszian disease definition, provided that AD bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 48 publications
(69 reference statements)
0
27
0
Order By: Relevance
“…AD is currently undergoing a conceptual transformation from a clinicopathological to a clinicobiological entity [3]. Such an approach enables the identification of AD in its oligosymptomatic stage, which is commonly termed mild cognitive impairment due to AD (MCI-AD) [4-6], or even before the onset of symptoms (i.e., the pre clinical stage).…”
Section: Introductionmentioning
confidence: 99%
“…AD is currently undergoing a conceptual transformation from a clinicopathological to a clinicobiological entity [3]. Such an approach enables the identification of AD in its oligosymptomatic stage, which is commonly termed mild cognitive impairment due to AD (MCI-AD) [4-6], or even before the onset of symptoms (i.e., the pre clinical stage).…”
Section: Introductionmentioning
confidence: 99%
“…Although most authors acknowledged that biomarker information enhances diagnostic accuracy [14-24] and validity is strong in selected cohorts [17-21, 25, 26], the predictive value was debated [14-34]. Many discussed the difficulty to discern normal aging from latent AD [14-16, 18, 20, 22, 25, 26, 28-30, 32, 33, 35], as the majority of cognitively healthy elderly with abnormal biomarkers never develop dementia [14-16, 20-23, 25, 26, 28-30, 32, 33, 36], since AD is multi-factorial [16, 18, 25, 26, 30, 34]. It was argued that procedures are not without burden or risk [14, 16, 18, 20, 21, 23, 24, 33] and consequences of incorrectly labeling people as ‘patients in waiting’ [24, 33] could be severe [14, 16, 24-27, 30].…”
Section: Resultsmentioning
confidence: 99%
“…It was argued that procedures are not without burden or risk [14, 16, 18, 20, 21, 23, 24, 33] and consequences of incorrectly labeling people as ‘patients in waiting’ [24, 33] could be severe [14, 16, 24-27, 30]. Most authors concluded that biomarker criteria require final demonstration of validity in populations without dementia [14-23, 25, 26, 29, 30, 32-34, 37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Alexopoulous and Kurz think there is practical validity in defining preclinical states of AD, such as by its effect on protective behaviors across the lifespan. However, they propose using the term "advanced brain aging" instead of "preclinical AD" on the grounds that they think a biomarker-based conceptualization of AD is conceptually invalid (Alexopoulos & Kurz, 2015). Although they are correct that AD biomarkers should be sufficiently validated and accurately distinguish between AD dementia and normal aging, AD neuropathology has been shown in a substantial number of brains of people aged less than 30 years Braak, Thal, Ghebremedhin, & Del Tredici, 2011; although, to be fair, not all such people will necessarily go on to develop AD symptoms in their old age).…”
Section: An Illustrative Example: Alzheimer Disease and Shifting Typomentioning
confidence: 99%